PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) STARBUCKS TERHADAP SOSIAL EKONOMI PETANI KOPI DI KARO SUMATERA UTARA - Eben Ezher Pakpahan; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to analyze the effect of Starbucks Corporate Social Responsibility (CSR) program on the socio-economic aspects of coffee farmers in Karo, North Sumatra. The purpose of this research is to find out and illustrate how Starbucks as a multi-national corporation effect the community groups where the company operates.. Indonesia is the 4th largest coffee producing country in the world. However, coffee farming in Indonesia still faces many obstacles so that the social and economic life of coffee farmers is not prosperous. Starbucks is a company with a commitment to making coffee as the first sustainable commodity in the world, this is achieved in various ways, including by ensuring the welfare of coffee farmers.This research is a qualitative research that explained based on the facts available. Neo-liberalism theory helps to analyze the role of non-state actors namely Multinational Corporation. Other theories used are the Corporate Social Responsibility Theory, and Theory of Effect, and Group Analysis which helps researchers find answers to the research problem. Data collection techniques used in this study were interviews, observation, library research.The results of this study indicate that two of Starbucks Corporate Social Responsibility programs have had an effect on the socio-economic conditions of coffee farmers in Karo, North Sumatra since the establishment of the Farmer Support Center in 2015. Through the program provided by Starbucks, coffee farmers have been able to increase the quality and quantity of coffee production, opening new business opportunities, increasing income, and supporting social activities of farmers. Keyword(s) : Starbucks, Effects, Farmer Support Center, Farmers, Karo District, Coffee Industry